The Potential of Telang Flower (Clitoria ternatea) in Functional Food Diversification in Indonesia - Puspitojati, Endah (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2024)
The telang flower (Clitoria ternatea) has been traditionally utilized as a natural dye and culinary component in numerous Asian countries, including Indonesia. Interest in telang flowers has surged in recent years because of its bioactive chemicals, particularly anthocyanins, which offer numerous potential health advantages. This article intends to thoroughly examine the use of telang flowers in Indonesia's food industry, emphasizing their nutritional properties, applications in diverse food and beverage products, and their potential to advance the functional food and nutraceutical sectors. This article discloses a recent study indicating that telang flowers have the potential to serve as a natural food with abundant health advantages, including antioxidant, anti-inflammatory, neuroprotective, antibacterial, and anti-asthmatic qualities. Moreover, telang flowers have been utilized in various foods, including tea, functional drinks, ice cream, etc, showcasing their adaptability in the culinary business. Nonetheless, other obstacles persist, including the absence of standardization in the production process, variability in the concentration of active chemicals attributable to environmental factors, and insufficient regulatory frameworks. This study aimed to explain comprehensive insights into the opportunities and challenges associated with optimizing telang flowers as an important element in the diversification of functional foods in Indonesia while also promoting further innovation in tcreatingnutraceutical products derived from natural ingredients.